7th Propulsion Joint Specialist Conference 1971
DOI: 10.2514/6.1971-735
|View full text |Cite
|
Sign up to set email alerts
|

On combustion generated noise

Abstract: Tn order to estimate the scaling rules for combustion noise, a tu -rb lence autocorrelation function of the reaction rate must be estimated. This depends in part upon the active reaction volume in a turbulent flame. This volume may be measured by direct flame photography centering on the radiation of an active radical in the reaction zone. The paper describes experiments on fuel-lean propane, propylene, and ethylene-air turbulent open premixed flames with burners of 0.4" -0.96" diameter and velocities to 600 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…The simple model delivers a conversion efficiency of η total ≈ 5.3 × 10 −6 -9.2 × 10 −6 and overpredicts the literature data [4,5] as well as the microphone measurements of the authors, which also show total efficiencies of η total ≈ 0.5 × 10 −7 -1.5 × 10 −7 , by at least one order of magnitude.…”
Section: Noise Production Efficiencymentioning
confidence: 49%
See 2 more Smart Citations
“…The simple model delivers a conversion efficiency of η total ≈ 5.3 × 10 −6 -9.2 × 10 −6 and overpredicts the literature data [4,5] as well as the microphone measurements of the authors, which also show total efficiencies of η total ≈ 0.5 × 10 −7 -1.5 × 10 −7 , by at least one order of magnitude.…”
Section: Noise Production Efficiencymentioning
confidence: 49%
“…While a literature study showed that the length scales were ranging from the laminar flame front thickness [5,19] to geometrical dimensions of the test rig [7], coherent length scales lying in between were found. Furthermore, the gap between theory and experiment mentioned by Strahle [5] of a factor of 100, could be allocated to non-stochastic, periodic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scales determine the possible size and frequency of noise sources inside the combustor. Early publications related to aero-and thermo-acoustics relied heavily on these scales in order to provide order-of-magnitude analysis of the noise which are still helpful [30,31]. While the experimental measurements allow only for temporal analysis of the data, since one-point LDV measurements were performed, the LES delivers also spatial information.…”
Section: Time and Length Scalesmentioning
confidence: 99%
“…In other words, the combustion process acts like a monopole. Strahle [3] published more theoretical studies. Based on Lighthill's procedure [4,5], he derived a wave equation using the conservation equation of multicomponent reacting flows.…”
Section: Introductionmentioning
confidence: 97%